Electrophysiological Anomalies in Face–Name Memory Encoding in Young Binge Drinkers - Folgueira-Ares, Rocío; Cadaveira, Fernando; Rodríguez Holguín, Socorro; López-Caneda, Eduardo; Crego, Alberto; Pazo-Álvarez, Paula (Frontiers in Psychiatry, 2017)
A growing body of evidence indicates that the intake of large amounts of alcohol during one session may have structural and functional effects on the still-maturing brains of young people. These effects are particularly pronounced in prefrontal and hippocampal regions, which appear to be especially sensitive to the neurotoxic effects of alcohol. However, to date, few studies have used the event related potentials (ERPs) technique to analyze the relationship between binge drinking and associative memory. The objective of this study was to examine brain activity during memory encoding using the Subsequent memory paradigm in subjects who have followed a binge drinking (BD) pattern of alcohol consumption for at least two years. A total of 50 undergraduate students (mean age = 20.6 years), i.e. 25 controls (12 females) and 25 binge drinkers (11 females), with no personal or family history of alcoholism or psychopathological disorders, performed a visual face-name association memory task. The task used enables assessment of the Difference due to memory effect (Dm), a measure of memory encoding based on comparison of the neural activity associated with subsequent successful and unsuccessful retrieval. In event-related potential (ERP) studies, study items that are subsequently remembered elicit larger positive amplitudes at midline parieto-frontal sites than those items that are subsequently forgotten. The Dm effect generally appears in the latency range of about 300-800 ms. The results showed a Dm effect in posterior regions in the 350-650 ms latency range in the Control group. However, in the BD group, no significant differences were observed in the electrophysiological brain activity between remembered and forgotten items during the encoding process. No differences between groups were found in behavioral performance. These findings show that young binge drinkers display abnormal pattern of ERP brain activity during the encoding phase of a visual face-name association task, possibly suggesting a different neural signature of successful memory encoding.